LUBAC assembles a ubiquitin signaling platform at mitochondria for signal amplification and transport of NF‐κB to the nucleus. (18th November 2022) - Wu, Zhixiao; Berlemann, Lena A; Bader, Verian; Sehr, Dominik A; Dawin, Eva; Covallero, Alberto; Meschede, Jens; Angersbach, Lena; Showkat, Cathrin; Michaelis, Jonas B; Münch, Christian; Rieger, Bettina; et al.
Abstract: Mitochondria are increasingly recognized as cellular hubs to orchestrate signaling pathways that regulate metabolism, redox homeostasis, and cell fate decisions. Recent research revealed a role of mitochondria also in innate immune signaling; however, the mechanisms of how mitochondria affect signal transduction are poorly understood. Here, we show that the NF‐κB pathway activated by TNF employs mitochondria as a platform for signal amplification and shuttling of activated NF‐κB to the nucleus. TNF treatment induces the recruitment of HOIP, the catalytic component of the linear ubiquitin chain assembly complex (LUBAC), and its substrate NEMO to the outer mitochondrial membrane, where M1‐ and K63‐linked ubiquitin chains are generated. NF‐κB is locally activated and transported to the nucleus by mitochondria, leading to an increase in mitochondria‐nucleus contact sites in a HOIP‐dependent manner. Notably, TNF‐induced stabilization of the mitochondrial kinase PINK1 furthermore contributes to signal amplification by antagonizing the M1‐ubiquitin‐specific deubiquitinase OTULIN. Overall, our study reveals a role for mitochondria in amplifying TNF‐mediated NF‐κB activation, both serving as a signaling platform, as well as a transport mode for activated NF‐κB to the nuclear. Synopsis: The E3 ubiquitin ligase HOIP is the catalytic component the linear ubiquitin chain assembly complex (LUBAC) that regulates canonical NF‐κB activation in innate immune signaling. This study reports a role of mitochondria in promoting TNF‐induced NF‐κB pathway activation by HOIP‐dependent reshaping of the mitochondrial membrane. LUBAC is recruited to the outer mitochondrial membrane upon TNF receptor activation. Formation of linear or M1‐linked ubiquitin chains enables the assembly of an NF‐κB signaling platform at mitochondria. PINK1 phosphorylates M1‐linked ubiquitin chains, which counteracts their OTULIN‐mediated hydrolysis. Mitochondrial motility facilitates shuttling of activated NF‐κB to the nucleus. TNF increases mitochondria‐ nucleus contact sites in a HOIP‐dependent manner. Abstract : TNF induces remodeling of the outer mitochondrial membrane by assembling an NF‐κB signaling platform that facilitates nuclear translocation of activated NF‐κB.